2014
DOI: 10.1038/nature13852
|View full text |Cite
|
Sign up to set email alerts
|

Luminal signalling links cell communication to tissue architecture during organogenesis

Abstract: Morphogenesis is the process whereby cell collectives are shaped into differentiated tissues and organs. The self-organizing nature of morphogenesis has been recently demonstrated by studies showing that stem cells in three-dimensional culture can generate complex organoids, such as mini-guts, optic-cups and even mini-brains. To achieve this, cell collectives must regulate the activity of secreted signalling molecules that control cell differentiation, presumably through the self-assembly of microenvironments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
156
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(166 citation statements)
references
References 39 publications
7
156
2
1
Order By: Relevance
“…Inhibition of Fgf signalling or lumen disassembly results in delayed deposition of the organs, whereas Fgf3 overexpression accelerates organ deposition (Durdu et al, 2014). Altogether, these findings show that Fgf signalling accounts for the directed motility of follower cells, acts as an attractive signal for proneuromasts, and regulates the deposition and thus patterning of centripetal organs (Chitnis et al, 2012;Dalle Nogare et al, 2014;Durdu et al, 2014;Lecaudey et al, 2008). Importantly, this dissection of the molecular networks that signal during pLL primordium migration has revealed the subtle changes in cell behaviours that are involved during this process.…”
Section: Epithelial-mesenchymal Transition (Emt)mentioning
confidence: 68%
See 1 more Smart Citation
“…Inhibition of Fgf signalling or lumen disassembly results in delayed deposition of the organs, whereas Fgf3 overexpression accelerates organ deposition (Durdu et al, 2014). Altogether, these findings show that Fgf signalling accounts for the directed motility of follower cells, acts as an attractive signal for proneuromasts, and regulates the deposition and thus patterning of centripetal organs (Chitnis et al, 2012;Dalle Nogare et al, 2014;Durdu et al, 2014;Lecaudey et al, 2008). Importantly, this dissection of the molecular networks that signal during pLL primordium migration has revealed the subtle changes in cell behaviours that are involved during this process.…”
Section: Epithelial-mesenchymal Transition (Emt)mentioning
confidence: 68%
“…During pLL primordium migration, Fgf signalling activity is required for the migration of follower cells adjacent to the leading domain, and for the formation and deposition of proneuromast rosettes (Chitnis et al, 2012;Dalle Nogare et al, 2014;Donà et al, 2013;Durdu et al, 2014;Lecaudey et al, 2008). Studies have shown that Fgf8-expressing/derived cells also contribute to molar placode formation; these cells likely form rosettes temporarily and show only minor displacement when Fgf8 activity is compromised (Prochazka et al, 2015).…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%
“…by combining intravital imaging of entire organisms with EM, which we here refer to as intravital CLEM Karreman et al, 2014Karreman et al, , 2016Maco et al, 2013). Intravital CLEM enabled important discoveries in several areas of life science, such as cell biology (Avinoam et al, 2015), neuroscience (Allegra Mascaro et al, 2013;Maco et al, 2013), cancer research (Karreman et al, 2016), virology (Hellström et al, 2015 and developmental biology (Durdu et al, 2014;Goetz et al, 2014), and is highly likely to contribute to future breakthroughs in biological research.…”
Section: Localization Microscopymentioning
confidence: 99%
“…In resin-and flat-embedded small organisms, it facilitates the retrieval of a precise ROI located within the intravital image and, for instance, afforded the characterization of how fibroblast growth factor (FGF) activity controls the frequency at which rosette-like mechanosensory organs, e.g. the zebrafish lateral line primordium, are deposited through the assembly of microluminal structures that constrain FGF signaling (Durdu et al, 2014). Studies performed in C. elegans provide additional examples of laser-assisted targeted ultramicrotomy; these have helped to further clarify at high resolution the formation of excretory canals, as well as the contribution of exosomes to alae formation (Hyenne et al, 2015) (Fig.…”
Section: Ground-breaking In Vitro Clemmentioning
confidence: 99%
See 1 more Smart Citation